In vitro morphogenetic response of sarcocornia ambigua - Rubio Gonçalves, Janaina; Roberto Zaffari, Gilmar (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Sarcocornia ambigua (Michx.) is a halophyte, which has a salt enriched with various minerals and low sodium content. This vegetable has pharmacological properties, of interest for the pharmaceutical and nutraceutical industry; however, there is no knowledge about the micropropagation of this vegetable. The present work evaluated the morphogenetic response of different explants in the in vitro culture of this species. The explants used were young and adult nodal segments, divided into apical, median and basal regions. The aseptic cultures were obtained from pre-disinfestation in 0.008% kasugamycin with neutral detergent and asepsis with 70% ethanol, 1% NaClO, 4% CaClO and 0.3% HgCl² . The seed multiplication was performed in semi-solid or liquid MS medium, added with growth regulators 0.5 mg / L NAA and 1.0 mg / L BAP, containing or not NaCl and natural sediment from the marsh environment. The highest percentage of aseptic cultures of Sarcocornia ambigua was obtained from the explants of apical and basal nodal segments with predisinfestation in Kasugamycin and disinfestation with the use of 70% ethanol and 1% CaClO. The concentration of 20 g/L NaCl in the culture medium resulted in the best in vitro morphogenetic response of the explants. The natural marsh substrate present in the culture medium provided maintenance of the green explants longer. Sarcocornia ambigua showed good morphogenetic response capacity in vitro, depending on the age and position of the branch that provided the explant and the composition of the culture medium.